Does Covid-19 Change The Stock Market Relationship With Interest-Exchange Rate? - Sun, Haorui; Hui, Janice Nga Lay; bin Pinjaman, Saizal; Yun, Wong Sing; Jia, Sun Hao; Lu, Qiu Qi (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2025)
Research Originality: Despite numerous studies conducted on similar topics, this study uniquely examines the short- and long-run dynamics of the interest rate, exchange rate, and stock prices in China under two distinct epochs: pre- and Covid-19 periods. Research Objectives: This study compares the impact of interest and exchange rates on the Chinese stock market during the COVID-19 and pre-COVID-19 periods. Furthermore, the study also investigated the speed of adjustment towards equilibrium following short-run shocks in the stock market. Research Method: This study employs monthly data on the Chinese stock market and the autoregressive distributed lag model-error correction model (ARDL-ECM) approach on a separate period. Empirical Results: On COVID-19, the interest rate and exchange rate are not jointly and individually cointegrated significantly in explaining the stock prices. Nevertheless, the short-run relationship is identified as significant for both variables. Meanwhile, during COVID-19, the variables are jointly significant, with the exchange rate also identified to explain the stock market movement in the long run individually. In the short run, despite the greater impact of the exchange rate, the interest rates have a hysteretic impact. Implications: The findings suggested that policymakers should leverage the exchange rate instrument as a better predictive tool in devising effective future policy-making. JEL Classification: C320, G11, G15